Epidemiology of dysplasia and carcinoma in situ of the cervix - Valdivia Ponce, Eduardo (2015)
The authors present a retrospective study of 60 patients with cervical dysplasia to demonstrate the linkages of dysplasia and cancer in situ. In addition an analysis of epidemiological factors linking estdas ending injury to sexual activity is.